Dynamic scene occlusion culling in 3D virtual environments - Paunoo, B. (Eurosis, Ghent Univ, 2004)
Visibility algorithms have recently regained attention because of the ever increasing size of polygon datasets in a scene and dynamic objects handling makes it impossible to display in real time with conventional approaches. Occlusion culling is one of the key techniques for output-sensitive rendering. Most of the scenes have major static objects and only a few of dynamic objects. Hence, an occlusion culling techniques developed for handling dynamic objects in static scenes using dynamic bounding volume where dynamic objects are wrapped in bounding volumes and inserted into spatial hierarchical data structure as a volume to avoid updating the structure for every dynamic object at each frame is created for each occluded dynamic object by using physical constraint of that object. This algorithm will be implemented using portal occlusion culling which is suitable for indoor and architectural scenes.